Asymmetric TDP pathology in primary progressive aphasia with right hemisphere language dominance. (30th January 2018) - Kim, Garam; Vahedi, Shahrooz; Gefen, Tamar; Weintraub, Sandra; Bigio, Eileen H.; Mesulam, Marek-Marsel; Geula, Changiz
Abstract : Objective: To quantitatively examine the regional densities and hemispheric distribution of the 43-kDa transactive response DNA-binding protein (TDP-43) inclusions, neurons, and activated microglia in a left-handed patient with right hemisphere language dominance and logopenic-variant primary progressive aphasia (PPA). Methods: Phosphorylated TDP-43 inclusions, neurons, and activated microglia were visualized with immunohistochemical and histologic methods. Markers were quantified bilaterally with unbiased stereology in language- and memory-related cortical regions. Results: Clinical MRI indicated cortical atrophy in the right hemisphere, mostly in the temporal lobe. Significantly higher densities of TDP-43 inclusions were present in right language-related temporal regions compared to the left or to other right hemisphere regions. The memory-related entorhinal cortex (ERC) and language regions without significant atrophy showed no asymmetry. Activated microglia displayed extensive asymmetry (R > L). A substantial density of neurons remained in all areas and showed no hemispheric asymmetry. However, perikaryal size was significantly smaller in the right hemisphere across all regions except the ERC. To demonstrate the specificity of this finding, sizes of residual neurons were measured in a right-handed case with PPA and were found to be smaller in the language-dominant left hemisphere. Conclusions: The distribution of TDP-43 inclusions and microglial activation in right temporal language regions showed concordance with anatomic distribution of cortical atrophy and clinical presentation. The results revealed no direct relationship between density of TDP-43 inclusions and activated microglia. Reduced size of the remaining neurons is likely to contribute to cortical atrophy detected by MRI. These findings support the conclusion that there is no obligatory relationship between logopenic PPA and Alzheimer pathology.